Hipster cafe location selection using spherical weighted arithmetic mean in topsis - Aziz, Nurul Suhada; Mohd Yussof, Muhammad Atiq Najmuddin; Che Su, Muhammad Afiq Adam; Mat Isa, Muhammad Syafiq (GADING Journal of Science and Technology, 2024)
In recent years, the popularity of hipster cafes has increased due to their modern, contemporary, and traditional ambiances, as well as the comfort of their patrons. Selecting an appropriate location is essential for the success of a hipster cafe. This paper suggests a technique termed The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) for the selection of an ideal location. The objective of this research is to utilize TOPSIS as a methodology to identify the optimal location for a hipster cafe. The factors or criteria considered included cost, location characteristics, target customers, and environmental factors. In addition, there are four other options to consider: Kota Bharu, Kubang Kerian, Machang, and Tanah Merah. The fuzzy questionnaire must be completed by three decision-makers chosen from the shareholders. The data was collected from decisionmakers and then processed using the Spherical Weighted Arithmetic Mean (SWAM) operator and aggregated weighted spherical fuzzy decision matrix. The Spherical Fuzzy Positive Ideal Solution (SF-PIS) and Spherical Fuzzy Negative Ideal Solution (SF-NIS) values are used to calculate the distance between alternatives. The value of the closeness ratio determines the rank of the alternatives. As a result, the alternative was chosen based on its ranking. According to the findings of this study, Kota Bharu has the highest closeness ratio compared to the other options.